Sosialisasi Pencegahan Pernikahan Dini Dan Seks Bebas - Amrina Rosyada; Andrian; Dian Indah Cahyani; Hufzon Azhari; Isni sapira; Julia Wahyuni Saputri; Liza Indah Safitri; Nurhidayah; Raodatul Hikmah; Rusdan Bakri; Wiwin Nurmayani; Surya Jagat, lalu (YAYASAN HAMJAH DIHA bekerjasama dengan PENA INSTITUTE, 2024)
This community service aims to provide outreach to students about the dangers of early marriage and free sex. Through this socialization activity on the prevention of early marriage and free sex, we are trying to increase students' and female students' awareness of the negative consequences of early marriage and free sex. This research involves a participatory approach, involving the community in planning and evaluating outreach activities.